Domestic Manufacturing Capabilities for Critical DoD Applications: Emerging Needs in Quantum-Enabled Systems: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
Recent advancements in quantum-enabled systems present a variety of new opportunities and challenges. These technologies are important developments for a variety of computing, communications, and sensing applications. However, many materials and components relevant to quantum-enabled systems exist outside of the United States, and it is important to promote the development of assured domestic sources of materials, manufacturing capabilities, and expertise.
Keywords: Computers and Information Technology

Disposal of Industrial and Domestic Wastes: Land and Sea Alternatives - National Research Council (The National Academies Press, 1984)
Can decision makers meaningfully compare land versus sea options for waste disposal? Using available scientific data on waste behavior and new studies from East and West Coast dump sites, this book shows how to use a matrix approach to rank the ecological and health consequences of any combination of waste, site, and disposal system design.
Keywords: Environment and Environmental Studies

Flying in the COVID-19 Era: Science-based Risk Assessments and Mitigation Strategies on the Ground and in the Air: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
The National Academies of Sciences, Engineering, and Medicine convened a workshop on February 4th and 5th, 2021 to review the issues related to safety of passengers and employees in commercial air transportation, for domestic and international travel, during the COVID-19 pandemic. The workshop explored best practices to assess and mitigate COVID-19 transmission risks experienced during the travel chain, from the departure airport entrance to the destination airport exit. The workshop also identified areas where more research is needed to address gaps in understanding. This publication documents the presentations and discussions held during the workshop, and is presented as a synthesis of the workshop.
Keywords: Space and Aeronautics

A Quadrennial Review of the National Nanotechnology Initiative: Nanoscience, Applications, and Commercialization - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2020)
Global advances in medicine, food, water, energy, microelectronics, communications, defense, and other important sectors of the economy are increasingly driven by discoveries in nanoscience and the development of nanotechnologies. Engaging the nanoscience and technology community in the crafting of national priorities, developing novel approaches for translating fundamental discovery to a technology readiness level appropriate for venture/industry funding, increasing domestic student interest in nanoscience to expand the workforce pipeline, and exploring new ways of coordinating the work of the National Nanotechnology Initiative (NNI) are all imperatives if the United States is to fully reap the societal benefits of nanotechnology. A Quadrennial Review of the National Nanotechnology Initiative provides a framework for a redesign of the NNI and its coordination with the goal of achieving a U.S. resurgence in nanotechnology. This report makes recommendations to improve the value of the NNI's research and development strategy and portfolio to the economic prosperity and national security of the United States.
Keywords: Engineering and Technology; Math, Chemistry, and Physics

Youth, Pornography, and the Internet - National Research Council (The National Academies Press, 2002)
The Internet has changed the way we access the world. This is especially true for kids, who soak up new technologies like eager little sponges. They have access to an enormous array of material, including educational links, sports info, chat rooms—and, unfortunately, pornography. But we must approach our need to protect children with care to avoid placing unnecessary restrictions on the many positive features of the Internet. Youth, Pornography, and the Internet examines approaches to protecting children and teens from Internet pornography, threats from sexual predators operating on-line, and other inappropriate material on the Internet. The National Research Council’s Computer Science and Telecommunications Board explores a number of fundamental questions: Who defines what is inappropriate material? Do we control Internet access by a 17-year-old in the same manner as for a 7-year-old? What is the role of technology and policy in solving such a problem in the context of family, community, and society? The book discusses social and educational strategies, technological tools, and policy options for how to teach children to make safe and appropriate decisions about what they see and experience on the Internet. It includes lessons learned from case studies of community efforts to intervene in kids’ exposure to Internet porn. Providing a foundation for informed debate, this very timely and relevant book will be a must-read for a variety of audiences.
Keywords: Behavioral and Social Sciences; Computers and Information Technology

U.S. Air Force Strategic Deterrence Analytic Capabilities: An Assessment of Tools, Methods, and Approaches for the 21st Century Security Environment - National Research Council (The National Academies Press, 2014)
Since the early 1960s, the U.S. strategic nuclear posture has been composed of a triad of nuclear-certified long-range bombers, intercontinental ballistic missiles, and submarine-launched ballistic missiles. Since the early 1970s, U.S. nuclear forces have been subject to strategic arms control agreements. The large numbers and diversified nature of the U.S. nonstrategic (tactical) nuclear forces, which cannot be ignored as part of the overall nuclear deterrent, have decreased substantially since the Cold War. While there is domestic consensus today on the need to maintain an effective deterrent, there is no consensus on precisely what that requires, especially in a changing geopolitical environment and with continued reductions in nuclear arms. This places a premium on having the best possible analytic tools, methods, and approaches for understanding how nuclear deterrence and assurance work, how they might fail, and how failure can be averted by U.S. nuclear forces. U.S. Air Force Strategic Deterrence Analytic Capabilities identifies the broad analytic issues and factors that must be considered in seeking nuclear deterrence of adversaries and assurance of allies in the 21st century. This report describes and assesses tools, methods - including behavioral science-based methods - and approaches for improving the understanding of how nuclear deterrence and assurance work or may fail in the 21st century and the extent to which such failures might be averted or mitigated by the proper choice of nuclear systems, technological capabilities, postures, and concepts of operation of American nuclear forces. The report recommends criteria and a framework for validating the tools, methods, and approaches and for identifying those most promising for Air Force usage.
Keywords: Conflict and Security Issues

Renewing U.S. Telecommunications Research - National Research Council (The National Academies Press, 2006)
The modern telecommunications infrastructure—made possible by research performed over the last several decades—is an essential element of the U.S. economy. The U.S. position as a leader in telecommunications technology, however, is at risk because of the recent decline in domestic support of long-term, fundamental telecommunications research. To help understand this challenge, the National Science Foundation asked the NRC to assess the state of telecommunications research in the United States and recommend ways to halt the research decline. This report provides an examination of telecommunications research support levels, focus, and time horizon in industry, an assessment of university telecommunications research, and the implications of these findings on the health of the sector. Finally, it presents recommendations for enhancing U.S. telecommunications’ research efforts.
Keywords: Computers and Information Technology; Engineering and Technology

Modeling the Economics of Greenhouse Gas Mitigation: Summary of a Workshop - National Research Council (The National Academies Press, 2011)
Models are fundamental for estimating the possible costs and effectiveness of different policies for reducing greenhouse gas (GHG) emissions. There is a wide array of models to perform such analysis, differing in the level of technological detail, treatment of technological progress, spatial and sector details, and representation of the interaction of the energy sector to the overall economy and environment. These differences impact model results, including cost estimates. More fundamentally, these models differ as to how they represent fundamental processes that have a large impact on policy analysis--such as how different models represent technological learning and cost reductions that come through increasing production volumes, or how different models represent baseline conditions. Reliable estimates of the costs and potential impacts on the United States economy of various emissions reduction and other mitigation strategies are critical to the development of the federal climate change research and development portfolio. At the request of the U.S. Department of Energy (DOE), the National Academies organized a workshop, summarized in this volume, to consider some of these types of modeling issues.
Keywords: Environment and Environmental Studies

Strategic Long-Term Participation by DoD in Its Manufacturing USA Institutes: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
The U.S. Department of Defense (DoD) Manufacturing USA Institutes aim to protect national security and increase U.S. competitiveness in manufacturing. The domestic industrial base is critical to supporting and sustaining both military advantage and economic competitiveness. Through these institutes, the DoD is committed to domestically designing and manufacturing the most innovative defense systems. Intended as intensely collaborative applied research and development endeavors among government, industry, and academia, the institutes are envisioned to become lasting, self-sustaining national assets. A long-term strategy is needed to achieve this goal. The National Academies of Sciences, Engineering, and Medicine recently convened a workshop to discuss the long-term sustainability of the Manufacturing USA Institutes. Participants explored different perspectives across multiple disciplines, discussed public-private partnership models, and considered international programs in advanced manufacturing to inform their recommendations regarding the future of the institutes. This publication summarizes the presentations and discussions from the workshop.
Keywords: Industry and Labor

Application of Lightweighting Technology to Military Aircraft, Vessels, and Vehicles - National Research Council (The National Academies Press, 2012)
Lightweighting is a concept well known to structural designers and engineers in all applications areas, from laptops to bicycles to automobiles to buildings and airplanes. Reducing the weight of structures can provide many advantages, including increased energy efficiency, better design, improved usability, and better coupling with new, multifunctional features. While lightweighting is a challenge in commercial structures, the special demands of military vehicles for survivability, maneuverability and transportability significantly stress the already complex process. Application of Lightweighting Technology to Military Vehicles, Vessels, and Aircraft assesses the current state of lightweighting implementation in land, sea, and air vehicles and recommends ways to improve the use of lightweight materials and solutions. This book considers both lightweight materials and lightweight design; the availability of lightweight materials from domestic manufacturers; and the performance of lightweight materials and their manufacturing technologies. It also considers the "trade space"--that is, the effect that use of lightweight materials or technologies can have on the performance and function of all vehicle systems and components. This book also discusses manufacturing capabilities and affordable manufacturing technology to facilitate lightweighting. Application of Lightweighting Technology to Military Vehicles, Vessels, and Aircraft will be of interest to the military, manufacturers and designers of military equipment, and decision makers.
Keywords: Engineering and Technology; Conflict and Security Issues

An Assessment of U.S.-Based Electron-Ion Collider Science - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2018)
Understanding of protons and neutrons, or "nucleons"—the building blocks of atomic nuclei—has advanced dramatically, both theoretically and experimentally, in the past half century. A central goal of modern nuclear physics is to understand the structure of the proton and neutron directly from the dynamics of their quarks and gluons governed by the theory of their interactions, quantum chromodynamics (QCD), and how nuclear interactions between protons and neutrons emerge from these dynamics. With deeper understanding of the quark-gluon structure of matter, scientists are poised to reach a deeper picture of these building blocks, and atomic nuclei themselves, as collective many-body systems with new emergent behavior.
Keywords: Math, Chemistry, and Physics

Review of Specialized Degree-Granting Graduate Programs of the Department of Defense in STEM and Management - National Research Council (The National Academies Press, 2014)
The United States military is arguably the most intensely technological, complex enterprise in existence. When compared to the gross domestic products of other countries, the Department of Defense (DoD) budget ranks above all but about 20 nations. If viewed as a company, it would be the largest globally with the most employees. Major investments in weapons systems using advanced technologies provide an advantage over competing systems. Each weapon, platform, vehicle, and person in an operating force is a node in one or more advanced networks that provide the ability to rapidly form a coherent force from a large number of broadly distributed elements. DoD's ability to create and operate forces of this nature demands a competent understanding by its workforce of the composition, acquisition, and employment of its technology-enabled forces. Review of Specialized Degree-Granting Graduate Programs of the Department of Defense in STEM and Management focuses on the graduate science, technology, engineering, mathematics and management (STEM+M) education issues of the Air Force, Navy, and Marines. This report assesses the cost, benefits, and organizational placement of DoD institutions that grant degrees in STEM+M and evaluates alternative ways - for example, civilian institutions and distance learning - to ensure adequate numbers and high-quality education outcomes for DoD personnel.
Keywords: Education

Privacy Research and Best Practices: Summary of a Workshop for the Intelligence Community - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
Recent disclosures about the bulk collection of domestic phone call records and other signals intelligence programs have stimulated widespread debate about the implications of such practices for the civil liberties and privacy of Americans. In the wake of these disclosures, many have identified a need for the intelligence community to engage more deeply with outside privacy experts and stakeholders. At the request of the Office of the Director of National Intelligence, the National Academies of Sciences, Engineering, and Medicine convened a workshop to address the privacy implications of emerging technologies, public and individual preferences and attitudes toward privacy, and ethical approaches to data collection and use. This report summarizes discussions between experts from academia and the private sector and from the intelligence community on private sector best practices and privacy research results.
Keywords: Computers and Information Technology; Conflict and Security Issues

Technology, Policy, Law, and Ethics Regarding U.S. Acquisition and Use of Cyberattack Capabilities - National Research Council (The National Academies Press, 2009)
The United States is increasingly dependent on information and information technology for both civilian and military purposes, as are many other nations. Although there is a substantial literature on the potential impact of a cyberattack on the societal infrastructure of the United States, little has been written about the use of cyberattack as an instrument of U.S. policy.
Keywords: Conflict and Security Issues; Computers and Information Technology

Decadal Survey of Civil Aeronautics: Foundation for the Future - National Research Council (The National Academies Press, 2006)
The U.S. air transportation system is very important for our economic well-being and national security. The nation is also the global leader in civil and military aeronautics, a position that needs to be maintained to help assure a strong future for the domestic and international air transportation system. Strong action is needed, however, to ensure that leadership role continues. To that end, the Congress and NASA requested the NRC to undertake a decadal survey of civil aeronautics research and technology (R&T) priorities that would help NASA fulfill its responsibility to preserve U.S. leadership in aeronautics technology. This report presents a set of strategic objectives for the next decade of R&T. It provides a set of high-priority R&T challenges—-characterized by five common themes—-for both NASA and non-NASA researchers, and an analysis of key barriers that must be overcome to reach the strategic objectives. The report also notes the importance of synergies between civil aeronautics R&T objectives and those of national security.
Keywords: Space and Aeronautics

High-Performance Structural Fibers for Advanced Polymer Matrix Composites - National Research Council (The National Academies Press, 2005)
Military use of advanced polymer matrix composites (PMC)—consisting of a resin matrix reinforced by high-performance carbon or organic fibers—while extensive, accounts for less that 10 percent of the domestic market. Nevertheless, advanced composites are expected to play an even greater role in future military systems, and DOD will continue to require access to reliable sources of affordable, high-performance fibers including commercial materials and manufacturing processes. As a result of these forecasts, DOD requested the NRC to assess the challenges and opportunities associated with advanced PMCs with emphasis on high-performance fibers. This report provides an assessment of fiber technology and industries, a discussion of R&D opportunities for DOD, and recommendations about accelerating technology transition, reducing costs, and improving understanding of design methodology and promising technologies.
Keywords: Engineering and Technology

Scientific Opportunities with a Rare-Isotope Facility in the United States - National Research Council (The National Academies Press, 2007)
Over ten years ago, U.S. nuclear scientists proposed construction of a new rare isotope accelerator in the United States, which would enable experiments to elucidate the important questions in nuclear physics. To help assess this proposal, DOE and NSF asked the NRC to define the science agenda for a next-generation U.S. Facility for Rare Isotope Beams (FRIB). As the study began, DOE announced a substantial reduction in the scope of this facility and put off its initial operation date by several years. The study focused on an evaluation of the science that could be accomplished on a facility reduced in scope. This report provides a discussion of the key science drivers for a FRIB, an assessment of existing domestic and international rare isotope beams, an assessment of the current U.S. position about the FRIB, and a set of findings and conclusions about the scientific and policy context for such a facility.
Keywords: Space and Aeronautics; Math, Chemistry, and Physics

Proceedings of the Materials Forum 2007: Corrosion Education for the 21st Century - National Research Council (The National Academies Press, 2007)
The U.S. industrial complex and its associated infrastructure are essential to the nation's quality of life, its industrial productivity, international competitiveness, and security. Each component of the infrastructure—such as highways, airports, water supply, waste treatment, energy supply, and power generation—represents a complex system requiring significant investment. Within that infrastructure both the private and government sectors have equipment and facilities that are subject to degradation by corrosion, which significantly reduces the lifetime, reliability, and functionality of structures and equipment, while also threatening human safety. The direct costs of corrosion to the U.S. economy represent 3.2 percent of the gross domestic product (GDP), and the total costs to society can be twice that or greater. Opportunities for savings through improved corrosion control exist in every economic sector.
Keywords: Engineering and Technology

Surviving Supply Chain Integration: Strategies for Small Manufacturers - National Research Council (The National Academies Press, 2000)
The managed flow of goods and information from raw material to final sale also known as a "supply chain" affects everything—from the U.S. gross domestic product to where you can buy your jeans. The nature of a company's supply chain has a significant effect on its success or failure—as in the success of Dell Computer's make-to-order system and the failure of General Motor's vertical integration during the 1998 United Auto Workers strike. Supply Chain Integration looks at this crucial component of business at a time when product design, manufacture, and delivery are changing radically and globally. This book explores the benefits of continuously improving the relationship between the firm, its suppliers, and its customers to ensure the highest added value. This book identifies the state-of-the-art developments that contribute to the success of vertical tiers of suppliers and relates these developments to the capabilities that small and medium-sized manufacturers must have to be viable participants in this system. Strategies for attaining these capabilities through manufacturing extension centers and other technical assistance providers at the national, state, and local level are suggested. This book identifies action steps for small and medium-sized manufacturers—the "seed corn" of business start-up and development—to improve supply chain management. The book examines supply chain models from consultant firms, universities, manufacturers, and associations. Topics include the roles of suppliers and other supply chain participants, the rise of outsourcing, the importance of information management, the natural tension between buyer and seller, sources of assistance to small and medium-sized firms, and a host of other issues. Supply Chain Integration will be of interest to industry policymakers, economists, researchers, business leaders, and forward-thinking executives.
Keywords: Engineering and Technology; Industry and Labor

What You Need to Know About Energy - National Research Council (The National Academies Press, 2008)
American society, with a standard of living unprecedented in human history, can attribute a large measure of its success to increasingly sophisticated uses of energy. But that condition has come at a cost to irreplaceable resources, to the environment, and to our national independence. The goal of What You Need to Know About Energy is to present an accurate picture of America's current and projected energy needs and to describe options that are likely to play a significant role in our energy future. Written for a general audience, the booklet begins with a description of the status of energy in 21st-century America, including an account of our main sources of energy and a survey of the nation's energy demand versus the world's available supply. It then looks ahead to the quest for greater energy efficiency and to a portfolio of emerging technologies.
Keywords: Energy and Energy Conservation; Engineering and Technology